Pharmacotherapy to prevent PTSD: Results from a randomized controlled proof-of-concept trial in physically injured patients - Stein, Murray B.; Kerridge, Carol; Dimsdale, Joel E.; Hoyt, David B. (Journal of traumatic stress, 2007)
Acute physical injury is frequently associated with mental health sequelae, which then accentuate disability and worsen functional outcomes. A pharmacological prevention approach to this problem has been proposed. This proof‐of‐concept study was a double‐blind, randomized controlled trial of 14 days of the beta‐blocker propranolol (n = 17), the anxiolytic anticonvulsant gabapentin (n = 14), or placebo (n = 17), administered within 48 hours of injury to patients admitted to a surgical trauma center. Of 569 accessible, potentially eligible subjects, 48 (8%) participated. Outcomes assessments were conducted at 1, 4, and 8 months postinjury. Although well tolerated, neither study drug showed a significant benefit over placebo on depressive or posttraumatic stress symptoms. Implications are discussed for future pharmacological prevention studies in survivors of acute traumatic injury.